Answer:
Simplifying
(4 + 2k) * 6 + 3k = 0
Reorder the terms for easier multiplication:
6(4 + 2k) + 3k = 0
(4 * 6 + 2k * 6) + 3k = 0
(24 + 12k) + 3k = 0
Combine like terms: 12k + 3k = 15k
24 + 15k = 0
Solving
24 + 15k = 0
Solving for variable 'k'.
Move all terms containing k to the left, all other terms to the right.
Add '-24' to each side of the equation.
24 + -24 + 15k = 0 + -24
Combine like terms: 24 + -24 = 0
0 + 15k = 0 + -24
15k = 0 + -24
Combine like terms: 0 + -24 = -24
15k = -24
Divide each side by '15'.
k = -1.6
Simplifying
k = -1.6
Explanation: